Effects of regular meditative practice on psychological measures of healthy subjects - Kelly Cristina Fernandes Rocha; Kliger Kissinger Fernandes Rocha; Regina Helena da Silva; Alessandra Mussi Ribeiro (Sociedade Brasileira de Medicina de Família e Comunidade, 2012)
Introduction: Meditation is described as a method for improving attention and promoting psychological and emotional stability, presenting favorable results on cognitive functions and stress tolerance as well. Recently, studies have shown differences on psychological measurements between meditators and non-meditators. The aim of this study was to investigate the influence of regular practice of meditation on psychological measures of healthy participants in basal conditions or after experimental stress-induction. Methods: Forty-four healthy participants (20 meditators and 24 non-meditators) were evaluated by inventories of life quality, anxiety, mood, sleep quality, depression, and stress. Furthermore, all participants were submitted to working memory tasks (Hanoy tower and Digit Spam) before and after two stress-induction procedures: Stroop Color-word and Serial Subtraction tests. The research protocol was approved by the institutional ethics committee (204/09 - CEP/UFRN, CAAE 0221.0.051.000-09). Results: Our results showed that meditators presented better inventories scores when compared with non-meditators in parameters such as life quality (score 15.6 versus 14.9, p = 0.04), mood (score 6.0 versus 22.5, p = 0.02), and depression (score 2.5 versus 7.0, p = 0.01). Regarding stress levels, 10 % of meditators (against 37.5% of non-meditators) presented low levels of stress (p = 0.04). Moreover, there was an improvement in performance of meditators (23.3 ± 0.8) in relation to non-meditators (19.0 ± 1.0) on digit span task and in Hanoi tower of meditators (165.2 ± 6.1 ) in relation to non-meditation (224.1 ± 13.1) after stress induction. Conclusion: These findings corroborate other studies showing that meditation can provide an improvement in general quality of life as well as the performance of practitioners in memory tasks.